2017
DOI: 10.1186/s12978-017-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two intervention models on contraceptive attitudes and behaviors among nulliparous women in Shanghai, China: a clustered randomized controlled trial

Abstract: BackgroundWith increasing acceptance of premarital sex among young Chinese women, the rates of unintended pregnancies and induced abortions are becoming alarmingly high, suggesting the needs of educating women with adequate contraceptive knowledge and providing them with accessible contraceptive services. Previous studies have shown that knowledge and attitudes towards contraception could be modified through intervention strategies. This study aimed to evaluate the effects of two community intervention models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…They also stated that we should teach proper fertility counseling using educational methods. [ 29 ] In his research, Morgan examined the knowledge gap associated with contraceptive methods in students. By providing educational interventions, Morgan showed that students do not have sufficient level of knowledge and awareness in the use of contraceptive methods, and this level is improved by performing educational interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They also stated that we should teach proper fertility counseling using educational methods. [ 29 ] In his research, Morgan examined the knowledge gap associated with contraceptive methods in students. By providing educational interventions, Morgan showed that students do not have sufficient level of knowledge and awareness in the use of contraceptive methods, and this level is improved by performing educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study is consistent with the results of research by Ramazani et al ., Modabber et al ., Alami et al ., Shokri et al ., He et al . [ 19 27 28 29 31 32 ] In the study of Ramazani et al . Entitled “The effect of premarital education and counseling program on the knowledge and attitude of couples towards reproductive health” a significant increase was observed in the mean score of couples' attitudes about reproductive health after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After randomisation, there will be seven clusters in the intervention group and six clusters in the control group. 23 …”
Section: Methods and Analysismentioning
confidence: 99%